IMPROVING NUMERACY LITERACY SKILLS THROUGH THE COLLABORATIVE LEARNING MODEL IN MATHEMATICS EDUCATION AT PRIMARY SCHOOLS - Muhamad Dias; Titim Fatimah; Muhammad Rifqi Mahmud (Universitas Majalengka, 2026)
This study was conducted to compare the application of collaborative learning and direct instruction models in improving numeracy skills among Year 5 primary school pupils. The research employed a quantitative approach using a quasi-experimental method and a pretest–posttest control group design. The research subjects were 40 Year 5 pupils at SDN 274 Cempaka Arum, Bandung, comprising 20 pupils in the experimental class and 20 in the control class. The results of the analysis showed that the pre-test mean scores for each class, as determined by the Mann-Whitney test, indicated no significant difference, as evidenced by the Asymp. Sig. value of 0.383 > 0.05. However, the N-Gain results revealed a significant difference between the classes. The results of the N-Gain calculation for the experimental class yielded an average of 0.71, falling into the high category. Meanwhile, the control class’s average was 0.39, falling into the moderate category. Inferential statistical analysis was then conducted, beginning with a normality test; however, as one dataset was not normally distributed, the Mann-Whitney test was used instead, yielding a significance value (one-tailed) of 0.001. Since the significance value (one-tailed) of 0.001 is less than 0.05, H0 is rejected and H1 is accepted. This means that the numeracy literacy skills of students using the collaborative learning model are better than those using the direct instruction model. Thus, the collaborative learning model is more effective in improving numeracy literacy skills than the direct instruction model.